EFFECTS OF AEROBIC EXERCISE TRAINING ON OXIDATIVE STRESS IN THE SKELETAL MUSCLES OF OBESE RATS - Ulbricht,Ariene Sampaio Souza Farias (2019)
ABSTRACT Introduction Obesity is a complex and multifactorial metabolic disorder characterized by the accumulation of body fat; physical exercise increases energy expenditure and promotes a reparative effect through modulation of endogenous antioxidant defenses. Objective To evaluate the effects of the high-fat diet (HFD) on oxidative stress parameters in skeletal muscles of rats using aerobic exercise training protocols (AETP), moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT). Methods The study was quantitative and experimental. Animals received 8 weeks of HFD or normal diet (ND), followed by 9 weeks of HFD or ND and the two AETPs. Results HFD did not alter the formation of thiobarbituric acid reactive substances (TBA-RS), total sulfhydryl and protein carbonyl content in the soleus and plantaris muscles; in contrast, the protocols caused a decrease in TBA-RS levels in the plantaris muscle and increased the sulfhydryl content in the soleus muscle, while MICT increased the sulfhydryl content in the plantaris muscle and reduced protein carbonyl content in both muscles. HFD reduced SOD activity in the plantaris muscle while the MICT protocol enhanced SOD in the soleus muscle and both protocols reversed the decrease in SOD in the plantaris muscle. HFD increased CAT activity in the soleus muscle, the HIIT protocol prevented this alteration and both protocols increased CAT in the plantaris muscle. HFD reduced GSH-Px activity in both muscles, and the MICT protocol prevented this reduction in the soleus muscle, while the HIIT protocol partially prevented this decrease. The MICT protocol did not prevent the reduction of GSH-Px and the HIIT protocol partially prevented this decrease in the plantaris muscle. Conclusions HFD elicited oxidative stress in the skeletal muscle of rats, and both protocols were able to prevent most of the alterations in oxidative stress parameters caused by the HFD. Level of evidence IV; Investigation of treatment outcomes.